Controlled chondrogenesis from adipose-derived stem cells by recombinant transforming growth factor-β3 fusion protein in peptide scaffolds. (1st January 2015) - Zheng, Dong; Dan, Yang; Yang, Shu-hua; Liu, Guo-hui; Shao, Zeng-wu; Yang, Cao; Xiao, Bao-jun; Liu, Xiangmei; Wu, Shuilin; Zhang, Tainjin; Chu, Paul K.
Graphical abstract: The addition of matrix metalloproteinases (MMPs) can trigger the long-term stable release of mTGF-β3 from the recombinant fusion protein of LAP-MMP-mTGF-β3 in the combined scaffolds, thus stimulating the differentiation of ADSCs into cartilage, which was confirmed by histological analysis, indicating the great potential of this hybrid in rapid therapy of osteoarthritis. Abstract: Adipose-derived stem cells (ADSCs) are promising for cartilage repair due to their easy accessibility and chondrogenic potential. Although chondrogenesis of transforming growth factor-β (TGF-β) mediated mesenchymal stem cells (MSCs) is well established in vitro, clinical tissue engineering requires effective and controlled delivery of TGF-β in vivo. In this work, a self-assembled peptide scaffold was employed to construct cartilages in vivo through the chondrogenesis from ADSCs controlled by recombinant fusion protein LAP-MMP-mTGF-β3 that was transfected by lentiviral vectors. During this course, the addition of matrix metalloproteinases (MMPs) can trigger the release of mTGF-β3 from the recombinant fusion protein of LAP-MMP-mTGF-β3 in the combined scaffolds, thus stimulating the differentiation of ADSCs into chondrogenesis. The specific expression of cartilage genes was analyzed by real-time polymerase chain reaction and Western blot. The expression of chondrocytic markers was obviously upregulated to a higher level compared to the one by commonly used TGF-β3 alone. After 3 weeks of in vitro culturing, the hybrids with differentiated chondrogenesis were then injected subcutaneously into nude mice and retrieved after 4 weeks of culturing in vivo. Histological analysis also confirmed that the recombinant fusion protein was more effective for the formation of cartilage matrix than the cases either with TGF-β3 alone or without LAP-MMP-mTGF-β3 ( P < 0.05). This study demonstrates that controlled local delivery of the LAP-MMP-mTGF-β3 constructs can accelerate differentiation of ADSCs into the cartilage in vivo, which indicates the great potential of this hybrid in rapid therapy of osteoarthritis.